How to promote university technology transfer? A configuration analysis based on technology, organization and environment framework. - Xin Wang (PLoS ONE)
University technology transfer (UTT) is at the forefront of innovation, representing the key to promoting the deep integration of science and technology with the economy. In order to explore mechanisms of realizing UTT, this study uses the fuzzy set qualitative comparative analysis (Fs-QCA) method to determine how the conditional configurations of technology, organization and environment (TOE) promote UTT. Evidently, there are four conditional configurations for promoting UTT, which are characterized by technology-organization-environment synergy, an organization-environment-orientation and a technology-organization-orientation. Technology transfer talents, organization construction, organization incentives, and market demand have an important influence on UTT. The main contribution of this study is its analysis of the nonlinear relationship between TOE conditions and UTT, which helps realize UTT in several ways.